Locally Unique Solutions of Quadratic Programs, Linear and Nonlinear Complementarity Problems - Mangasarian, Olvi (University of Wisconsin-Madison Department of Computer Sciences, 1979)
It is shown that McCormick's second order sufficient optimality conditions are also necessary for a solution to a quadratic program to be locally unique and hence these conditions completely characterize a locally unique solution of any quadratic program. This result is then used to give characterizations of a locally unique solution to the linear complementarity problem. Sufficient conditions are also given for local uniqueness of solutions of the nonlinear complementarity problem.